GUESS NUMBERS GAME APPLICATIONS USING VISUAL BASIC PROGRAMMING LANGUAGES RELEASE 6.0 - R. Jenar Kusbandono; Ristyawati Ristyawati,SKom,MMSI (Jurnal Sistem Informasi, 2005)
Writing applications contain about a computer game applications. In the writing ofthis game applications, the author outlines a few things about Visual Basicprogramming language, game programs and matters related to the computer gameitself.In this paper the author makes a Windows-based computer game using Visual BasicRelease 6.0.